The Effect of the Initial Impressions about the Text Strategy on Developing Expressive Performance among Second Intermediate Grade Students (Journal of the College of Basic Education, 2026)
The aim of this study is to identify the effect of the “Initial Impressions Strategy” about a text on developing expressive performance among second-grade intermediate students. To achieve this goal, the researcher adopted the quasi-experimental method with two groups—an experimental group and a control group—using a series of post-tests.The research sample consisted of 78 students, divided equally between the two groups (39 students in the experimental group and 39 in the control group). Equivalence between the groups was established in the following variables: chronological age (measured in months), scores on the linguistic ability test, Arabic language subject scores in the mid-year exam, parents’ educational attainment, and Raven’s Progressive Matrices intelligence test.The experimental group was taught using the Initial Impressions about the Text strategy, while the control group was taught using the conventional method. The researcher prepared eight instructional lesson plans for each group and formulated 64 behavioral objectives distributed across the six levels of Bloom’s taxonomy.A standardized instrument was developed to measure expressive performance, consisting of a series of post-tests. The researcher employed the following statistical methods: the t-test for independent samples, Chi-square (χ²), Samir Nov test, Levene’s test, and Eta squared (η²) coefficient. The results were analyzed statistically to reach conclusions, recommendations, and suggestions.